The modernization of Feedwater Pump Turbine (FWPT) controller for nuclear power plants unit 5 and 6 - Sohn, Kwangyoung; Lee, Jayoung; Cho, Changhwan (Transactions on Engineering and Computing Sciences, 2015)
For modernization, Feedwater Pump Turbine (FWPT) for HANUL Nuclear Power Plants Unit 5 & 6 has been replaced with Triple Modular System including the upgrade of control logic actuating Low Pressure/High Pressure (LP/HP) stop valves and control valves. This modernization includes hardware platform change as well as ladder logic changes. This paper provides the lesson learned from the design support and the verification and validation (V&V) for control logic software in accordance with IEEE 1012[1], which describes the Software Development Life Cycle (SDLC) phase activities for independent verification and validation (V&V). As usually it is necessary to interpret standards by upward and/or downward tailoring, i.e. interpretation, based on the SIL level and application function for practical independent V&V. It has been conducted to list up the inspection viewpoints for software itself as well as architectural design including the hardware interfaces. For successful independent V&V of FWPT, the specific viewpoints and approach are employed according to the functional characteristics and code optimization. The V&V for this project reviews only the requirement, design, implementation, and test phase. This article also provides the difficulty experienced during independent V&V including the design support, and concludes by addressing a couple of lessons learned for FWPT V&V.